Success and failure of cardiovascular disease prevention in Czech Republic over the past 30 years. Czech part of the EUROASPIRE I-IV surveys - Rosolová, H; Nussbaumerová, B; Mayer, O; Cífková, R; Bruthans, J (Physiological research, 2017)
Cardiovascular (CV) mortality was reduced more than 50 % in the Czech population at the turn of the century, due to an improvement of major CV risk factors in the general population, interventional procedures implemented into the treatment of acute coronary events, and new drugs (ACE inhibitors, statins etc.) for CV prevention (Czech MONICA and post-MONICA studies, 1985-2008). An insufficient level of preventive efforts is described in the Czech patients after acute coronary syndrome (Czech part of the EUROASPIRE studies, 1995-2013). Drug underdosing and wrong patients' compliance to life style and drug therapy recommendations represent two main reasons of this unsatisfactory situation. The residual vascular risk of patients with stable coronary heart disease (CHD) is still high due to a poor control of conventional risk factors on the one hand, and due to increasing weight and glucose metabolism abnormalities on the other hand. Patients with insulin resistance and glucose disorders have more frequently non LDL C dyslipidemia (atherogenic dyslipidemia), hypertriglyceridemic waist and high atherogenic index of plasma (AIP>0.24), i.e. markers of residual CV risk. Among others increased dose of statins and combined lipid modifying therapy should be implemented in patients with CHD, diabetes or metabolic syndrome.
Keywords: rizikové faktory; kardiovaskulární nemoci; Česká republika; Time Factors; časové faktory; Risk Factors; zdravotnické přehledy; lidé; Health Surveys; sekundární prevence; Secondary Prevention; Cardiovascular Diseases; Treatment Failure; Czech Republic; neúspěšná terapie; Humans